Ensuring a Fair Development? The Role of Cohesion Policy and Just Transition Mechanism in the EU Green Initiative - Li, Hang (Review of European and Comparative Law, 2025)
The dual imperatives of environmental sustainability and equitable development occupy a central position in the EU’s strategic vision, yet their concurrent pursuit engenders inherent tensions. The EU has noted that some regions and people are more vulnerable in the process of realizing green ambitions and that the Just Transition Mechanism (JTM) and Cohesion Policy (CP) are two of the most crucial concepts and tools for the EU to mitigate this friction in order to mediate between socio-economic equity and the realization of green ambitions. This article examines how the EU’s CP and JTM reconcile environmental climate goals with social fairness, especially the potential challenges and interactions in this process. Combining legal analysis of EU treaties and funding regulations with policy evaluations of subsidy implementation, it identifies a divergence in primary objectives between the CP’s regional balanced development goals and the JTM’s mandate to mitigate the social impact of urgent decarbonization. The study argues that achieving a fair green transition requires a wider interpretation of “Just Transition” under EU climate law. It proposes harmonizing the CP and JTM, and sets the functionalism as the core to determine the integrative relationship between the CP and JTM. Furthermore, enforceable and convenient procedural rights for affected populations is a feasible way to improve the supporting effect of related structural funds. By addressing normative gaps in participatory equity, this analysis advances institutional pathways to align environmental urgency with just development in supranational policymaking and implementation.